MODERN TRENDS IN DISTANCE LEARNING IN HIGHER EDUCATIONAL INSTITUTIONS - Кириченко, Тетяна (SWorldJournal, 2024)
The article examines current trends in the development of distance learning in higher education institutions of Ukraine. The author analyses the key aspects of distance learning, identifying priority areas, including infrastructure and technical support,